Method for manufacturing an electrode and electrode
Patent Information
- Application Number
- CN202580020153.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-22
- Filing Date
- 2025-03-11
- Publication Date
- 2026-10-20
AI Technical Summary
[0012]根据本公开,能够提供可得到连续的复合材料片的电极的制造方法。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This disclosure relates to a method for manufacturing an electrode and the electrode itself. Background Technology
[0002] Electrodes for non-aqueous electrolyte secondary batteries such as lithium-ion batteries are typically manufactured using a wet method: coating a slurry of an electrode composite material containing active materials and binders onto the surface of a core material serving as a metal foil, followed by drying and compression of the coating. In recent years, a dry method has been studied, where electrode composite material powder is stretched into sheets to form composite sheets, which are then bonded to the core material to manufacture the electrode. Patent Document 1 discloses an electrode composite sheet manufactured by mixing active materials, binders such as polytetrafluoroethylene (PTFE), and conductive materials using a mill, and then fiberizing the PTFE. Techniques for fiberizing binders are also disclosed, for example, in Patent Documents 2 and 3.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Publication No. 2019-512872
[0006] Patent Document 2: Japanese Patent Publication No. 2020-510961
[0007] Patent Document 3: Japanese Patent Publication No. 2023-549248 Summary of the Invention
[0008] However, in the dry process, if the PTFE used as the binder is not sufficiently fiberized, even if it is desired to make composite sheets from electrode composites, it is impossible to form composite sheets while maintaining the powder state of the electrode composites, or even if it is possible to form composite sheets, the composite sheets will break in the middle, making it difficult to obtain continuous composite sheets.
[0009] Therefore, the purpose of this disclosure is to provide a method for manufacturing electrodes that can produce continuous composite material sheets.
[0010] The electrode manufacturing method disclosed herein is characterized by comprising: a mixing step in which an electrode composite material containing an active substance and polytetrafluoroethylene and having a solid component concentration substantially 100% is mixed at a temperature of 70°C or higher to fiberize the polytetrafluoroethylene; and a composite material sheet manufacturing step in which the electrode composite material formed by fiberizing the polytetrafluoroethylene is shaped into a sheet to produce a composite material sheet, wherein in the mixing step, mixing is performed until the degree of fiberization of the polytetrafluoroethylene reaches 1.4% by mass or higher.
[0011] The electrode disclosed herein is characterized in that it has a core material and a composite material sheet disposed on the core material, the composite material sheet being a sheet of the electrode composite material obtained by mixing an electrode composite material containing an active substance and polytetrafluoroethylene with a solid content of substantially 100% at a temperature of 70°C or higher, thereby fiberizing the polytetrafluoroethylene, wherein the degree of fiberization of the polytetrafluoroethylene is 1.4% by mass or higher.
[0012] According to this disclosure, a method for manufacturing electrodes that yields continuous composite material sheets can be provided. Attached Figure Description
[0013] Figure 1 This is a diagram showing the mixing process for compounding electrode composite materials.
[0014] Figure 2 This diagram illustrates the composite sheet manufacturing process, which involves making composite sheets from electrode composite materials.
[0015] Figure 3 This diagram illustrates the bonding process of joining the surface of the composite material sheet to the core material. Detailed Implementation
[0016] Hereinafter, embodiments of the electrodes involved in this disclosure will be described in detail. The embodiments described below are merely examples, and this disclosure is not limited to the embodiments described below. The accompanying drawings referred to in the description of the embodiments are schematic illustrations, and the size ratios of the constituent elements depicted in the drawings should be determined with reference to the following description. In addition, configurations that selectively combine the various embodiments and variations described below are included in this disclosure.
[0017] The electrodes and manufacturing methods disclosed herein are suitable for non-aqueous electrolyte secondary batteries such as lithium-ion secondary batteries, but can also be applied to energy storage devices such as batteries or capacitors containing aqueous electrolytes. The electrodes and manufacturing methods disclosed herein can be applied to both negative and positive electrodes. It should be noted that the following description uses electrodes for non-aqueous electrolyte secondary batteries as examples.
[0018] The following is for reference Figures 1-3 The manufacturing method of the electrode is described. The electrode is manufactured through a mixing process and a composite material sheet fabrication process.
[0019] (Mixing process)
[0020] The mixing process is as follows: An electrode composite material containing active material and polytetrafluoroethylene (PTFE) with a solid content substantially 100% is mixed at a temperature above 70°C, thereby fiberizing the PTFE. For example, as... Figure 1As shown, an electrode composite material 20 containing active material and particulate polytetrafluoroethylene is kneaded using a stirring device 30 equipped with stirring blades 30b mounted on a rotating shaft 30a. Although not shown, a heating device, such as a heater, is provided on the outer wall of the stirring device 30. During kneading, the electrode composite material 20 is heated using the heating device to a temperature of 70°C or higher. By kneading the electrode composite material 20 at a temperature of 70°C or higher, the fiberization of the polytetrafluoroethylene is promoted.
[0021] In the mixing process, mixing continues until the degree of fiberization of polytetrafluoroethylene (PTFE) reaches 1.4% by mass or more. This allows for the formation of a continuous composite sheet from the electrode composite material 20 in the subsequent stage. From the viewpoint of obtaining a continuous composite sheet, a degree of fiberization of PTFE of 1.4% by mass or more is acceptable, preferably 3.0% by mass or more, and more preferably 6.0% by mass or more. The upper limit of the degree of fiberization of PTFE can, for example, be 10.0% by mass or less.
[0022] The degree of fibrillation of polytetrafluoroethylene (PTFE) can be adjusted by controlling the temperature and Froude number during the mixing of the electrode composite material 20. From the viewpoint of promoting PTFE fibrillation, the mixing temperature is preferably 70°C or higher, more preferably 90°C or higher, and more preferably 100°C or higher. Considering the thermal stability of PTFE, the upper limit of the temperature is preferably 300°C or lower. From the viewpoint of promoting PTFE fibrillation, the Froude number is preferably 8.84 or higher. The upper limit of the Froude number is not particularly limited, for example, it is 50.0 or lower. The Froude number is defined as follows.
[0023] The Froude number is a dimensionless number representing the ratio of the force acting on an object to gravity. When mixing electrode composite materials using a stirring device with stirring blades set on a rotating shaft, it can be calculated using the following formula.
[0024]
[0025] v is the circumferential velocity of the stirring blade (m / s), and r is the radius of rotation of the stirring blade (m). It should be noted that the radius of rotation is the length from the axis of rotation to the tip of the stirring blade. g is the acceleration due to gravity, which is 9.8 m / s². 2 The circumferential speed v (m / s) of the rotating blade is calculated from the circumference (m) of the circle with radius (m) r of the stirring blade and the rotational speed (rpm). It should be noted that, as... Figure 1 As shown in the stirring device 30, when there are multiple stirring blades, the largest Froude number among those calculated based on the circumferential speed and rotation radius of each stirring blade is defined as the Froude number specified in this embodiment. For example, in Figure 1When the three stirring blades of the stirring device 30 shown have different circumferential speeds and rotation radii, the largest of the three Froude numbers calculated based on the circumferential speeds and rotation radii of these three different stirring blades is preferably 8.84 or higher.
[0026] The degree of fibrillation of polytetrafluoroethylene (PTFE) in the electrode composite material 20 is difficult to determine in its powder state; therefore, it is measured by molding the electrode composite material 20 into a composite sheet. In this embodiment, composite sheets are prepared from each electrode composite material obtained by pre-mixing various mixing conditions such as mixing temperature (70°C or higher) and Froude number. The degree of PTFE fibrillation is measured from each prepared composite sheet, and mixing conditions of 1.4% by mass or higher are derived. Then, the derived conditions are used as the conditions for achieving a degree of PTFE fibrillation of 1.4% by mass or higher in the electrode composite material, and the actual mixing process is performed. The determination of the degree of PTFE fibrillation is described below.
[0027] In the compounded electrode composite material 20, in addition to polytetrafluoroethylene (PTFE), it may also contain binder material components other than PTFE, such as polyvinylidene fluoride (PVdF). The average particle size of the granular PTFE before fiberization is not particularly limited, but is, for example, 100 μm or more and 500 μm or less. The average particle size can be determined by observing the PTFE particles using a scanning electron microscope (SEM). Specifically, based on extracting 100 randomly selected particles, the diameter of the circumscribed circle of each of the 100 particles is measured, and the measured values are averaged to obtain the average particle size. The PTFE content is preferably 0.1 parts by mass or more and 5.0 parts by mass or less, more preferably 0.2 parts by mass or more and 3 parts by mass or less, relative to 100 parts by mass of the active material.
[0028] As the active material used in manufacturing the positive electrode, lithium transition metal composite oxides, for example, can be used. Examples of metal elements contained in the lithium transition metal composite oxide include Ni, Co, Mn, Al, B, Mg, Ti, V, Cr, Fe, Cu, Zn, Ga, Sr, Zr, Nb, In, Sn, Ta, and W. Preferably, it contains at least one element selected from Ni, Co, and Mn. In particular, as a component of the lithium transition metal composite oxide, the proportion of Ni among the metal elements other than lithium is preferably 70% or more and 99% or less, more preferably 80% or more and 95% or less. Relative to the total amount of the electrode composite material 20, the content of the positive electrode active material is preferably 85% by mass or more and 99% by mass or less, more preferably 90% by mass or more and 98% by mass or less (the preferred content of the negative electrode active material is also the same as the content of the positive electrode active material).
[0029] The positive electrode active material is composed, for example, of secondary particles formed by the aggregation of multiple primary particles. The median particle size (D50) of the positive electrode active material in a volumetric reference is preferably 3 μm or more and 30 μm or less. D50 refers to the particle size at which the cumulative frequency in the volumetric particle size distribution reaches 50% from the smallest end; it is also called the median diameter. The particle size distribution of the positive electrode active material can be measured using a laser diffraction-type particle size distribution measuring device (e.g., Microtrac BEL Co., Ltd., MT3000II) with water as the dispersion medium.
[0030] As active materials for manufacturing the negative electrode, carbon-based active materials such as natural graphite (e.g., flake graphite, block graphite, amorphous graphite) and artificial graphite (e.g., blocky graphite, graphitized mesophase carbon microspheres, MCMB) can be used. Active materials containing Si, Sn, etc., alloyed with lithium can also be used as negative electrode active materials.
[0031] The electrode composite material 20 being compounded may contain a conductive material. In particular, when manufacturing a positive electrode, it is preferable to contain a conductive material. Examples of conductive materials include carbon black such as acetylene black and Ketjen black, carbon nanotubes (CNTs), and carbon materials such as graphite. A preferred example of the content of the conductive material is 0.2% by mass or more and 5.0% by mass or less.
[0032] When the electrode composite material 20 includes a conductive material, the active material, polytetrafluoroethylene (PTFE), and the conductive material can be mixed together. However, it is preferable to first prepare a composite material with the conductive material attached to the surface of the active material, and then mix this composite material and PTFE as the electrode composite material 20. The composite material is obtained by mixing the active material and the conductive material in a mixing granulator, a particle compounding device, or similar apparatus. Examples of such apparatus include, for instance, the NOB300-NOBILTA (registered trademark) and MECHANOFUSION (registered trademark) manufactured by Hosokawa Micron Co., Ltd., the Hybridization System manufactured by Nara Machinery Manufacturing Co., Ltd., the FM mixer and COMPOSI manufactured by Nippon Coke Industry Co., Ltd., the high-speed mixer manufactured by EARTHTECHNICA Co., Ltd., the high-power mixer manufactured by Nippon Erich Co., Ltd., the balance granulator manufactured by Freund-Turbo Co., Ltd., and the vertical granulator manufactured by POWREX Co., Ltd.
[0033] Through kneading, the electrode composite material 20 formed by fibrillating polytetrafluoroethylene, that is, the electrode composite material 20 containing an active material, fibrillated polytetrafluoroethylene, and an optional conductive material, can be subjected to a particle size regulation treatment. In the particle size regulation treatment, for example, after the electrode composite material 20 is pulverized (finely pulverized) by a pulverizer, the pulverized electrode composite material 20 is sieved by a classifier, thereby regulating the particle size of the electrode composite material 20.
[0034] (Composite Material Sheet Production Step)
[0035] The composite material sheet production step is a step of forming the electrode composite material 20, in which polytetrafluoroethylene is fibrillated through the kneading step, into a sheet shape, thereby producing the composite material sheet 12. For example, as shown in Figure 2 , the electrode composite material 20 in which polytetrafluoroethylene is fibrillated through the kneading step is fed to a pair of rolls 31, and is calendered through the gap formed between the pair of rolls 31, thereby obtaining the sheet-shaped composite material sheet 12. It should be noted that Figure 2 the rotation axes of the respective rolls shown are parallel, and the arrows drawn on the respective rolls indicate the rotation directions of the respective rolls.
[0036] The thickness of the composite material sheet 12 can be controlled, for example, by the gap between the rolls, the peripheral speed of the rolls, the number of passes through the rolls, and the like. For example, rolls having a peripheral speed ratio differing by 2 times or more may be used to form the electrode composite material 20 into a sheet shape. By making the peripheral speed ratios of the rolls different, thinning of the composite material sheet 12 becomes easy, and productivity is improved. In addition, in the composite material sheet production step, the composite material sheet 12 may finally be compressed. The line pressure at this time is, for example, 1 t / cm or more and 3 t / cm or less.
[0037] The composite material sheet 12 has an active material and fibrillated polytetrafluoroethylene. The composite material sheet 12 may contain a conductive material. In particular, when the composite material sheet 12 is applied to a positive electrode, it preferably contains a conductive material. The fibrillation degree of polytetrafluoroethylene contained in the composite material sheet 12 is 1.4 mass% or more as described above. The fibrillation degree of polytetrafluoroethylene (PTFE) is calculated as follows.
[0038] <Method for Calculating Fibrillation Degree of PTFE>
[0039] (1) The surface of the composite material sheet is observed by energy-dispersive X-ray spectroscopy (EDX) to obtain a mapped image in which a region where carbon element exists (C region), a region where oxygen element exists (O region), a region where fluorine element exists (F region), and a region where a transition metal element (for example, Ni) contained in the active material exists (hereinafter referred to as Ni region) are mapped. The magnification of EDX is adjusted so that an image with a size of 300 μm in length × 400 μm in width is obtained.
[0040] (2) Import the mapped image into a computer and use image analysis software (such as ImageJ, manufactured by the National Institutes of Health) to obtain a first composite image in which the repeated parts of the Ni, C and O regions are regarded as “regions where active substances and conductive materials exist (regions where the object exists)”; a second composite image in which the repeated parts of the Ni, C, F and O regions are regarded as “regions where fibrous PTFE on active substances and conductive materials exist (regions where the object exists)”; and a third composite image in which the repeated parts of the C, F and O regions are regarded as “regions where aggregated PTFE and conductive materials exist (regions where the object exists)”.
[0041] (3) Using image analysis software, calculate the number of pixels occupied by the “area where the object exists” in each of the first to third composite images, and calculate the area ratio of the fibrous part using the following formula.
[0042] The area ratio (%) of the fibrous portion = the area where the object exists in the second composite image / (the area where the object exists in the first composite image + the area where the object exists in the second composite image + the area where the object exists in the third composite image)
[0043] (4) In the second composite image, calculate the ratio of fluorine to all elements to obtain "the amount of F present in the fibrous part (mass%)".
[0044] (5) The degree of fibrosis of PTFE is calculated based on the following formula from the above-mentioned "area ratio of fibrous part (%)" and "amount of F present in fibrous part (mass %)".
[0045] The degree of fibrillation of PTFE (mass %) = the area ratio of fibrillated portions × the amount of F present in the fibrillated portions.
[0046] (6) Perform (1) to (5) on two different parts of the composite material sheet respectively, and take the average value of the obtained values as the degree of fiberization (mass %) of PTFE in the electrode composite material.
[0047] The resulting composite material sheet 12 is surface-bonded to the core material 11 (bonding process). In the bonding process, for example, as... Figure 3 As shown, the composite material sheet 12 and the core material 11 are passed between a pair of rollers 32, thereby bonding the surfaces of the composite material sheet 12 and the core material 11 (bonding process). This results in an electrode with the composite material sheet 12 disposed on the core material 11. As described above, the degree of fiberization of the polytetrafluoroethylene contained in the composite material sheet 12 is 1.4% by mass or more.
[0048] exist Figure 3In this configuration, composite material sheets 12 are bonded to only one surface of the core material 11, but they can also be bonded to both surfaces of the core material 11. In this case, two composite material sheets 12 can be bonded to both surfaces of the core material 11 simultaneously, or the first composite material sheet 12 can be bonded to one surface of the core material 11, and then the second composite material sheet 12 can be bonded to the other surface of the core material 11.
[0049] At least one of the pair of rollers 32 can be heated. The temperature of these rollers is preferably room temperature to 300°C or less, more preferably room temperature to 200°C or less. The linear pressure between the pair of rollers 32 is, for example, 0.1 t / cm or more and 2 t / cm or less. An intermediate layer such as an adhesive layer may also be formed on both sides of the core material 11 supplied for this bonding process.
[0050] Furthermore, a compression process can be performed on the electrode obtained in this way, as needed. Specifically, the electrode can be fed into a predetermined gap between a pair of opposing rollers and compressed by that gap. The linear pressure between the pair of rollers that compress the electrode is, for example, 1 t / cm or more and 3 t / cm or less.
[0051] The core material 11 can be a metal foil or a thin film with a metal layer formed on its surface. The thickness of the core material 11 is, for example, 5 μm or more and 20 μm or less. When the electrode is a positive electrode, a metal foil such as aluminum or an aluminum alloy can be used as the core material 11. When the electrode is a negative electrode, a metal foil such as copper or a copper alloy can be used as the core material 11.
[0052] The thickness of the composite material sheet 12 is, for example, 50 μm or more and 150 μm or less, preferably 80 μm or more and 140 μm or less, and more preferably 100 μm or more and 130 μm or less.
[0053] The resulting electrode can be applied to long strip electrodes constituting a wound electrode body, or to rectangular electrodes constituting a stacked electrode body.
[0054] Example
[0055] The present disclosure is further illustrated below by way of examples, but the present disclosure is not limited to these examples.
[0056] <Example 1>
[0057] [Fabrication of positive electrode composite sheet]
[0058] Using a mixer, 100 parts by mass of Ni-Co-Al (NCA) based lithium transition metal composite oxide, serving as the positive electrode active material, and 0.9 parts by mass of carbon black, serving as the conductive material, were mixed to prepare a conductive material coating of the positive electrode active material, where the conductive material adheres to the particle surface of the positive electrode active material. An electrode composite material, consisting of 100 parts by mass of this conductive material coating of the positive electrode active material, with 0.8 parts by mass of polytetrafluoroethylene particles added and a solid content concentration of 100%, was then mixed using mixing apparatus A at 70°C and a Froude number of 17.68. The aforementioned Froude number is defined as follows: the circumferential speed of the shredder (rotating blades) mounted on the rotating shaft is v, the rotation radius of the shredder is r, and the gravitational acceleration g is 9.8 m / s². 2 To calculate.
[0059] The mixed electrode composite material is sieved for granulation. The rectified electrode composite material is then passed between a pair of opposing rollers to form a sheet, thus obtaining a composite material sheet.
[0060] The degree of fiberization of polytetrafluoroethylene in the electrode composite material was determined from the obtained composite sheet, and the result was 1.8% by mass. In addition, the composite sheet did not break midway during the forming process, and a continuous composite sheet could be formed.
[0061] <Example 2>
[0062] As for the mixing conditions of the electrode composite material, the temperature was set to 90°C, and the circumferential speed v of the shredder was changed to set the Froude number to 8.84. Otherwise, the composite sheet was formed in the same manner as in Example 1. The degree of fiberization of polytetrafluoroethylene in the electrode composite material was measured from the obtained composite sheet, and the result was 6.0% by mass. Moreover, in Example 2, the composite sheet did not break during the forming process, and a continuous composite sheet could be formed.
[0063] <Example 3>
[0064] As for the mixing conditions of the electrode composite material, the temperature was set to 100°C, the circumferential speed v of the shredder was changed, and the Froude number was set to 8.84. Otherwise, the composite sheet was formed in the same manner as in Example 1. The degree of fiberization of polytetrafluoroethylene in the electrode composite material was measured from the obtained composite sheet, and the result was 4.3% by mass. Moreover, in Example 3, the composite sheet did not break during the forming process, and a continuous composite sheet could be formed.
[0065] <Example 4>
[0066] As for the mixing conditions of the electrode composite material, mixing apparatus B, which has a different rotation radius r from mixing apparatus A, was used. The temperature was set to 100°C, and the circumferential speed of the shredder was changed to set the Froude number to 10.64. Otherwise, the composite material sheet was formed in the same manner as in Example 1. The degree of fibrillation of polytetrafluoroethylene in the obtained composite material sheet was measured, and the result was 3.8% by mass. Moreover, in Example 4, the composite material sheet did not break during the forming process, and a continuous composite material sheet could be formed.
[0067] <Example 5>
[0068] As for the mixing conditions of the electrode composite material, the temperature was set to 100°C, and the composite sheet was formed in the same manner as in Example 1. The degree of fiberization of polytetrafluoroethylene in the electrode composite material was measured from the obtained composite sheet, and the result was 3.3% by mass. Moreover, in Example 5, the composite sheet did not break midway during the forming process, and a continuous composite sheet could be formed.
[0069] <Example 6>
[0070] As for the mixing conditions of the electrode composite material, the temperature was set to 150°C, and the composite sheet was formed in the same manner as in Example 1. The degree of fiberization of polytetrafluoroethylene in the obtained composite sheet was measured, and the result was 6.7% by mass. Moreover, in Example 6, the composite sheet did not break during the forming process, and a continuous composite sheet could be formed.
[0071] <Comparative Example 1>
[0072] As for the mixing conditions of the electrode composite material, the temperature was set to 20°C, and the composite sheet was formed in the same manner as in Example 1. The degree of fiberization of polytetrafluoroethylene in the electrode composite material was measured from the obtained composite sheet, and the result was 1.3% by mass. Moreover, in Comparative Example 1, the composite sheet broke midway during the forming process, and it was impossible to form a continuous composite sheet.
[0073] <Comparative Example 2>
[0074] As for the mixing conditions of the electrode composite material, the temperature was set to 50°C, and the composite material sheet was formed in the same manner as in Example 1. The degree of fiberization of polytetrafluoroethylene in the electrode composite material was measured from the obtained composite material sheet, and the result was 1.0% by mass. Moreover, in Comparative Example 1, the composite material sheet broke midway during the forming process, and it was impossible to form a continuous composite material sheet.
[0075] <Comparative Example 3>
[0076] As for the mixing conditions of the electrode composite material, the temperature was set to 100°C, the circumferential speed v of the shredder was changed and the Froude number was set to 4.2. Otherwise, it was carried out in the same way as in Example 1. As a result, even when the mixed electrode composite material was passed between a pair of opposing rollers, it was not possible to form a composite sheet in a powder state.
[0077] Table 1 summarizes the mixing conditions and film formation results of the composite sheets in each embodiment and comparative example.
[0078] [Table 1]
[0079]
[0080] Based on the results of each embodiment and comparative example, in the mixing process of mixing an electrode composite material containing an active substance and polytetrafluoroethylene with a solid component concentration of substantially 100% at a temperature of 70°C or higher to fiberize the polytetrafluoroethylene, the mixing is carried out until the degree of fiberization of the polytetrafluoroethylene reaches 1.4% by mass or more. As a result, during the process of forming a composite material sheet from the mixed electrode composite material, the composite material sheet will not break in the middle and a continuous composite material sheet can be formed.
[0081] Explanation of reference numerals in the attached figures
[0082] 11 Core material, 12 Composite material sheet, 20 Electrode composite material, 30 Stirring device, 30a Rotating shaft, 30b Stirring blade, 31, 32 Rollers.
Claims
1. A method for manufacturing an electrode, characterized in that, It has the following characteristics: The mixing process involves mixing an electrode composite material containing active material and polytetrafluoroethylene with a solid content of substantially 100% at a temperature above 70°C, thereby fiberizing the polytetrafluoroethylene. as well as The composite material sheet manufacturing process involves shaping the electrode composite material, which is made of polytetrafluoroethylene fibers, into a sheet shape, thereby producing the composite material sheet. In the mixing process, the polytetrafluoroethylene is mixed until the degree of fibrillation of the polytetrafluoroethylene reaches 1.4% by mass or more.
2. The method for manufacturing the electrode according to claim 1, wherein, In the mixing process, a stirring device equipped with stirring blades mounted on a rotating shaft is used to mix the mixture at a temperature of 70°C or higher and a Froude number of 8.84 or higher.
3. An electrode having a core material and a composite material sheet disposed on the core material, The composite material sheet is formed by mixing an electrode composite material containing active substances and polytetrafluoroethylene (PTFE) with a solid content substantially 100% at a temperature above 70°C, thereby fiberizing the PTFE. The degree of fibrillation of the polytetrafluoroethylene is 1.4% by mass or more.
Citation Information
Patent Citations
Electrode for energy storage device and method for manufacturing dry electrode film for energy storage device
JP2019512872A
Prelithiated Hybrid Energy Storage Devices
JP2020510961A
A method for producing freestanding electrode membranes using a wet process that does not use organic solvents
JP2023549248A